Motivasi Kader Terhadap Pelayanan Posyandu Balita - Wiwin Rohmawati (Universitas Muhammadiyah Klaten, 2020)
Posyandu (Integrated Service Post) is a form of Community-Based Health Efforts (UKBM) carried out by, from and with the community, to empower and provide facilities for the community to obtain health services for mothers, babies and toddlers (Ministry of Health, 2012). Motivation is a force that describes both extrinsic conditions that stimulate certain behaviors and intrinsic responses that reveal human behaviors (Swanburg, 2006). The purpose of this study was to determine the relationship between cadres' motivation and posyandu services for toddlers in the Polanharjo Klaten area. The research method used was descriptive correlational with cross sectional approach. The population in this study were 50 posyandu cadres in Kapungan village and Polanharjo Klaten village. The sampling technique in this study was total sampling, the instrument used was the Kendall tau data analysis questionnaire. The results of the characteristics of the respondents included cadres age 41-50 years, education was mostly high school, most of the respondents' occupation was IRT. The study showed that there were high cadres of motivation (42%) and the posyandu services for toddlers were sufficient (84%). Cadre suggestions can improve their performance by actively attending and participating in posyandu cadre training so that the implementation of posyandu can be up to standard.